P260 An analysis of non-melanoma skin cancer rates in the tofacitinib Ulcerative Colitis clinical programme. (27th May 2021) - Sands, B E; Cohen, R D; Ha, C; Reinisch, W; Salese, L; Mundayat, R; Lawendy, N; Panés, J
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). We present an updated analysis of non-melanoma skin cancer (NMSC) events in the tofacitinib UC clinical programme, including final data from the open-label, long-term extension (OLE) study (as of 24 Aug 2020). Methods: NMSC events were evaluated from 3 randomised, placebo (PBO)-controlled studies (2 Phase [P]3 induction studies [NCT01465763; NCT01458951]; 1 P3 maintenance study [NCT01458574]) and an OLE study (NCT01470612), as 3 cohorts: Induction (P3 induction studies [patients (pts) receiving tofacitinib 10 mg twice daily (BID) or PBO]); Maintenance (P3 maintenance study [pts receiving tofacitinib 5 or 10 mg BID or PBO]); Overall (pts receiving tofacitinib 5 or 10 mg BID in P3 or OLE studies). Analysis was by predominant dose (PD) 5 or 10 mg BID, based on average daily dose <15 or ≥15 mg, respectively (82% of pts received PD 10 mg BID). An independent adjudication committee reviewed potential NMSC. Proportions and incidence rates (IRs; unique pts with events per 100 pt-years of exposure) were evaluated for NMSC. A Cox proportional hazards model was used for risk factor analysis. Results: 1124 pts were evaluated for NMSC (2809.4 pt-years of tofacitinib exposure; up to 7.8 years of treatment; median duration 685.5 days). NMSC events in Induction and Maintenance were previously reported (Table 1). 1 In Overall, NMSC occurred in 21 pts (IR 0.73 [95% confidence interval (CI) 0.45, 1.12]): PD tofacitinib 5 mg BID n=5, IR 0.63 (0.21, 1.48); PD tofacitinib 10 mg BID n=16, IR 0.77 (0.44, 1.25) (Table 1); 2 new cases since May 2019. 1 Eleven pts had squamous cell carcinoma and 15 pts had basal cell carcinoma; 5 pts had both. No NMSC was metastatic or led to discontinuation. IRs by time interval and subgroup are reported (Table 2). Prior NMSC (hazard ratio [HR] 12.08 [95% CI 4.20, 34.76]) and age (per 10-year increase, HR 2.01 [1.38, 2.93]) were significant risk factors for NMSC in the multivariable analysis. Prior immunosuppressant use was not a significant risk factor in either the multivariable or univariate analyses. Conclusion: In this analysis, NMSC IRs for tofacitinib were similar to those in pts with UC treated with biologics 2 and those previously reported in the tofacitinib UC clinical programme. 1 NMSC events were more likely to occur in pts with recognised NMSC risk factors: prior NMSC and increasing age. 3 Dose dependency of NMSC IR could not be concluded here, as dose changes were permitted. NMSC IRs remained stable over time, up to 7.8 years of exposure. References: Sands et al. United European Gastroenterol J 2020;8(S):P0498 Curtis et al. Inflamm Bowel Dis 2020;Epub ahead of print, 3. Marcil, Stern. Arch Dermatol 2000;136:1524–30